2007
DOI: 10.1111/j.1532-5415.2007.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Collaborative Approach on the Quality of Prescribing for Geriatric Inpatients: A Randomized, Controlled Trial

Abstract: OBJECTIVES: To evaluate the effect of pharmaceutical care provided in addition to acute Geriatric Evaluation and Management (GEM) care on the appropriateness of prescribing. DESIGN: Randomized, controlled trial, with the patient as unit of randomization. SETTING: Acute GEM unit. PARTICIPANTS: Two hundred three patients aged 70 and older. INTERVENTION: Pharmaceutical care provided from admission to discharge by a specialist clinical pharmacist who had direct contacts with the GEM team and patients. MEASURE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
262
2
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(287 citation statements)
references
References 48 publications
13
262
2
10
Order By: Relevance
“…In agreement with these results, a previous study showed a reduction in the number of drugs with at least one inappropriate rating after implementation of the LIMM model [10]. A number of earlier controlled studies on pharmaceutical care, integrated medicines management or other collaborative approaches in hospitalised patients have also shown improvements in the appropriateness of medications (decrease in the MAI scores) [9,28,29].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In agreement with these results, a previous study showed a reduction in the number of drugs with at least one inappropriate rating after implementation of the LIMM model [10]. A number of earlier controlled studies on pharmaceutical care, integrated medicines management or other collaborative approaches in hospitalised patients have also shown improvements in the appropriateness of medications (decrease in the MAI scores) [9,28,29].…”
Section: Discussionsupporting
confidence: 73%
“…Nonetheless, we have presented the MAI scores in this study in order to facilitate comparison with previous studies. In our study, the average patient MAI score in the intervention group at discharge was lower than that in most other studies (indicating more appropriate prescribing) [9,10,28,29]. However, because the control group also had a very low patient MAI score, there were no apparent differences between the groups.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Strategies that were shown to be effective in reducing the use of PIMs include provider education and detailed assessment of home medication lists upon hospital admission by a multidisciplinary team, which involves geriatricians and specialized clinical pharmacists [22][23][24][25]. Polypharmacy should provoke attempts to stop unnecessary medications and drugs that are prone to be prescribed inappropriately; CNS-active drugs, PPIs, NSAIDs, NOACs, diuretics, and digoxin should be carefully evaluated and monitored.…”
Section: Discussionmentioning
confidence: 99%